Straining metal electrodes AS a SCC test. Type 304 stainless steel in MgCI2, Ca CI2 and LicI solutions - Maier, Irene Ana; López Pérez, E.; Galvele, José Rodolfo (Pergamon Press, 1982)
Fil: Maier, Irene Ana Comisión Nacional de Energía Atómica; Argentina